On weak compactness of bounded sets in Banach and locally convex spaces - Kogut, P. I.; Mel'nik, V. S. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We investigate the compactness of one class of bounded subsets in Banach and locally convex spaces. We obtain a generalization of the Banach-Alaoglu theorem to a class of subsets that are not polars of convex balanced neighborhoods of zero.